The influence of parents' knowledge on HPV vaccine uptake — evidence from Albania - Çela, Miranda; Gjata, Elinda; Sinaj, Enkeleda; Ndreu, Vjollca; Gega, Migena; Dervishi, Orgeta; Neçaj, Ledi; Refatllari, Brizida; Sinaj, Esmeralda; Kamberi, Fatjona (The Journal of Infection in Developing Countries, 2025)
Introduction: Despite the HPV vaccine's efficacy in cervical cancer prevention, cervical cancer ranks second in prevalence among women, following breast cancer. Various factors negatively impact HPV vaccination uptake, with parents' knowledge and attitudes being particularly crucial in this regard. Methodology: A cross-sectional study was conducted between February and May 2023, targeting parents in northern Albania. The standardized Vaccination and HPV Knowledge (THinK) questionnaire was used, and a random sampling methodology was applied. Data were collected at primary healthcare centers, targeting parents who were seeking various healthcare services. Results: A total of 102 participants completed the questionnaire, yielding a response rate of 74%. The majority of parents were married (79.4%), female (82.4%), over 30 years of age, and residents of urban areas (67.6%). A low mean score was reported for both the vaccination rate of girls (1.79 ± 0.40) and the willingness to vaccinate them (1.31 ± 0.46). Of the participants, 15 (14.7%) parents expressed strong knowledge of vaccines, while only 6 (5.9%) had knowledge about HPV, and 52 (51%) expressed interest in receiving information about HPV vaccination. Three factors emerged, explaining 71.02% of the variance: knowledge about HPV and vaccination, side effects of the vaccines, and the impact of vaccinating girls on HPV vaccination uptake. Conclusions: The study found that the identified factors—knowledge, side effects of vaccines, and vaccination attitudes—significantly influence HPV vaccination uptake. Co-creation activities involving parents, girls, and healthcare professionals are the most effective strategies to build trust and improve awareness among the target population regarding the HPV vaccine.